Inhibition of Apoptosis in Periodontitis - Lucas, H.; Bartold, P.M.; Dharmapatni, A.A.S.S.K.; Holding, C.A.; Haynes, D.R. (Journal of dental research, 2010)
This study investigated whether the prolonged survival of inflammatory cells in periodontal disease could be due to the inhibition of apoptosis by tumor necrosis factor-related apoptosis-inducing ligand (TRAIL) decoy receptors and inhibition of the terminal stages of apoptosis signaling by inhibitor of apoptosis (IAP) family members. Gingival tissue samples were taken from healthy individuals and those with chronic periodontitis. The expression of TRAIL, TRAIL receptors, TUNEL, cleaved caspase-3, xIAP, and survivin was determined immunohistologically and at the level of mRNA expression. Higher levels of TRAIL and the TRAIL decoy receptor, TRAIL R4, were expressed in the diseased periodontal tissues (p < 0.005). Statistically (p < 0.05) higher levels of cleaved caspase-3 and the cleaved caspase-3 inhibitors, xIAP and survivin, were seen. Similar changes were seen at the level of mRNA. The results indicate that apoptosis in periodontitis may be inhibited by elevated expression of TRAIL decoy receptors and cleaved caspase-3 inhibitors.